Prevalence of Porphyromonas gingivalis and its relationship with herpesvirus in Indian subjects with chronic periodontitis: A cross-sectional study - Vinayak M Joshi; Kishore G Bhat; Manohar S Kugaji; Preeti S Ingalagi (Wolters Kluwer Medknow Publications, 2016)
Background: Porphyromonas gingivalis (P. gingivalis) is a periodontal pathogen that is commonly harbored in the dental plaque of humans. The aim of this study was to look into the prevalence of P. gingivalis and its association with herpesvirus in Indian subjects. This is probably the first study on the association of this bacterium with herpesvirus in Indians. Materials and Methods: This cross-sectional study consists of 200 subjects, with 100 subjects each in the healthy group and the chronic periodontitis (CP) group. Upon plaque collection, one portion of the samples was immediately plated, on culture media that is selective for P. gingivalis. Total colony-forming units (CFU)/mL from each plate was recorded. The remaining plaque sample was subjected to DNA extraction and polymerase chain reaction (PCR) was performed using specific primers for Cytomegalovirus (CMV) and Epstein-Barr virus (EBV). The data are analyzed using the chi-square test, Spearman's rho correlation coefficient, and Mann-Whitney U test. Results: P. gingivalis was detected in 66% of the subjects with CP and in 40% in the healthy group, and this difference was statistically significant (P = 0.00023). The correlation of clinical parameters with P. gingivalis showed a significant positive correlation, indicating that higher levels of clinical parameters were associated with higher CFUs of P. gingivalis in culture. The comparison of the presence of P. gingivalis between herpesvirus-negative and -positive cases showed that CMV-positive cases had significantly higher levels of this bacterium. Conclusions: The results of this study confirmed the earlier finding of P. gingivalis presence in significantly higher levels in CP subjects and in CMV-positive sites. In addition, there was a positive association of the bacterium with clinical parameters.